Compensation and moral luck - Heinzelmann, Nora (The monist, 2021)
In some vicarious cases of compensation, an agent seems obligated to compensate for a harm they did not inflict. This raises the problem that obligations for compensation may arise out of circumstantial luck. That is, an agent may owe compensation for a harm that was outside their control. Addressing this issue, I identify five conditions for compensation from the literature: causal engagement, proxy, ill-gotten gains, constitution, and affiliation. I argue that only two of them specify genuine and irreducible grounds for compensation, and that factors determining the agent’s obligations may be beyond their control. However, I suggest that this is unproblematic. There is thus no problem of circumstantial moral luck for compensation.